«Hórrido yermo de inflamada arena». Cienfuegos and Romantic Cosmic Pain - Russell P. SEBOLD (Cuadernos Dieciochistas)
It was painful to be a journalist and poet with noble aspirations for reform during the reign of Charles IV. in the years immediately preceding, nine well known Spanish poets had already expressed in romantic form their deep anxiety and insecurity regarding the universe in which they dwelt. One of them, Meléndez Valdés, inventor of the Spanish name for romantic cosmic grief, fastidio universal, was Cienfuegos’s poetic mentor and friend. the present article explains how Cienfuegos joined the European and Spanish philosophical and literary traditions that led to the poetic expression of the afflicted romantic mentality, and how he at the same time became an outstanding innovator in this tradition.